Corn stigma wall-broken decoction piece HPLC fingerprint spectrum and construction method and application thereof
Through HPLC technology and specific pretreatment and analysis methods, the HPLC fingerprint map of corn shavings broken wall decoctions was established, solving the problem of difficulty in monitoring and detecting the quality of corn shavings broken wall decoctions in the prior art, and achieving a more comprehensive and objective quality assessment.
Patent Information
- Application Number
- CN202411946950.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-12-26
AI Technical Summary
The prior art is difficult to effectively monitor and quality detection of corn shaved broken wall decoctions, especially when changes in dissolution of their chemical compositions lead to inapplicability of traditional detection methods.
High performance liquid chromatography (HPLC) technology combined with specific pretreatment methods and analysis methods to establish an HPLC fingerprint of corn shaved broken wall decoctions, and quality control and detection are carried out through this map.
A more comprehensive and objective quality assessment of corn shaved broken wall decoctions is achieved, ensuring the overall quality and stability of the product, and providing an applicable quality inspection method.
Smart Images

Figure CN119804747A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of traditional Chinese medicine analysis and detection, and in particular to an HPLC fingerprint of corn silk wall-broken pieces and a construction method and application thereof. Background Art
[0002] Corn silk (Stigma mydis) is the dried style and stigma of corn. It was first recorded in the Compendium of Materia Medica in my country. It is sweet and light in taste, neutral in nature, and enters the bladder, liver, and gallbladder meridians. It has the effects of diuresis and swelling, clearing the liver and gallbladder, and clearing away heat and reducing fire. Modern pharmacological studies have shown that corn silk has a variety of biological activities, such as anti-tumor, antioxidant, hypoglycemic, and anti-inflammatory. At present, the research on the chemical composition of corn silk is not thorough enough, and due to the different climates and corn varieties in different regions, the appearance and chemical composition of corn silk will vary to a certain extent.
[0003] Corn silk broken wall slices are made from corn silk slices, processed into powder with D90 <45μm (above 300 mesh) by traditional Chinese medicine wall breaking technology, and then bonded and formed with water or ethanol of different concentrations to form uniform dry granular slices with all the original ingredients of 30-100 mesh. Compared with traditional corn silk slices, corn silk broken wall slices have the advantages of uniform quality, high drug utilization rate, good stability and convenient and quick application. However, breaking the wall will bring about changes in the solubility of chemical components such as effective ingredients or index ingredients, making the identification and quality inspection methods of traditional corn silk powder or corn silk formula granules not fully applicable to corn silk broken wall slices.
[0004] Therefore, in order to more comprehensively monitor the quality of corn silk broken wall slices, improve the quality evaluation system of corn silk broken wall slices, and establish a fingerprint of corn silk broken wall slices with good separation and comprehensive chromatographic peaks, it is of great significance. Summary of the invention
[0005] In order to overcome the above-mentioned defects and shortcomings in the prior art, the present invention provides an HPLC fingerprint of corn silk broken wall slices and a construction method and application thereof.
[0006] The first object of the present invention is to provide a pretreatment method for detecting corn silk broken wall pieces by high performance liquid chromatography.
[0007] The second object of the present invention is to provide a high performance liquid chromatography analysis method.
[0008] The third object of the present invention is to provide the application of any of the above-mentioned pretreatment methods and / or high performance liquid chromatography analysis methods in establishing the HPLC fingerprint of corn silk broken wall pieces and / or the quality control of corn silk broken wall pieces.
[0009] The fourth object of the present invention is to provide a method for constructing an HPLC fingerprint of corn silk broken wall pieces.
[0010] The fifth object of the present invention is to provide a quality detection method for corn silk broken wall pieces.
[0011] Therefore, the present invention claims the following:
[0012] A pretreatment method for detecting corn silk broken wall pieces by high performance liquid chromatography comprises the following steps:
[0013] S1. Mix the sample to be tested with methanol and perform ultrasound, cool it, use methanol to make up for the weight loss, separate the solid and liquid, and remove the methanol in the liquid;
[0014] S2. dissolving the product of step S1 in water, adding ethyl acetate for extraction, taking the ethyl acetate layer and removing the ethyl acetate to obtain a residue;
[0015] S3. Dissolve the residue in methanol, filter with a microporous membrane, and take the filtrate.
[0016] The corn silk broken wall slices are provided by Zhongshan Zhongzhi Chinese Medicine Pieces Co., Ltd., and the sample meets the quality standard requirements of "Guangdong Province Chinese Medicine Broken Wall Pieces Quality Standard Research Specifications (Trial)".
[0017] Preferably, in step S1, the mass volume ratio of the sample to be tested to methanol is 1 g: (12-13) mL.
[0018] More preferably, in step S1, the mass volume ratio of the sample to be tested to methanol is 1 g:12.5 mL.
[0019] Preferably, in step S1, the ultrasonication time is 25 to 35 minutes.
[0020] More preferably, in step S1, the ultrasonication time is 30 min.
[0021] Preferably, the frequency of the ultrasound is 35-45 kHz, and the power is 490-630 W.
[0022] More preferably, the frequency of the ultrasound is 40 kHz and the power is 560 W.
[0023] Preferably, in step S2, the extraction is performed 2 to 3 times.
[0024] More preferably, in step S2, the extraction is performed twice.
[0025] Preferably, the mass volume ratio of the sample to be tested to water is 1 g: (7-8) mL.
[0026] More preferably, the mass volume ratio of the sample to be tested to water is 1 g:7.5 mL.
[0027] Preferably, in step S2, the volume ratio of water to ethyl acetate is (0.8-1.2) mL:1 mL.
[0028] More preferably, in step S2, the volume ratio of water to ethyl acetate is 1 mL:1 mL.
[0029] Preferably, in step S3, the pore size of the microporous filter membrane is 0.45 μm.
[0030] A high performance liquid chromatography analysis method comprises the following steps:
[0031] Reference solution: ferulic acid solution;
[0032] Test solution: Prepare using any of the above pretreatment methods;
[0033] Chromatographic conditions: Octadecylsilane bonded silica gel is used as the filler of the chromatographic column, acetonitrile is used as the mobile phase A, and a phosphoric acid solution with a volume fraction of 0.28-0.32% is used as the mobile phase B. In the gradient elution program, the volume percentage of mobile phase A in the mobile phase system changes as follows:
[0034] From 0 to 8 min, mobile phase A increased from 10% to 19%;
[0035] 8-13 min, mobile phase A is 19%;
[0036] From 13 to 55 min, mobile phase A increased from 19% to 45%;
[0037] From 55 to 65 min, mobile phase A increased from 45% to 68%;
[0038] 65-80 min, mobile phase A is 68%;
[0039] At 80-85 min, mobile phase A was reduced from 68% to 10%;
[0040] The detection wavelength is 273 nm, and the theoretical plate number calculated based on ferulic acid should be no less than 10,000.
[0041] Preferably, the preparation method of the ferulic acid solution is: fully mixing ferulic acid and methanol, and the mass volume ratio of ferulic acid to methanol is (245-255) μg:1 mL.
[0042] More preferably, the mass volume ratio of ferulic acid to methanol is 250 μg:1 mL.
[0043] Preferably, the injection volume of the reference solution and the test solution is 8-12 μL.
[0044] More preferably, the injection volume of the reference solution and the test solution is 10 μL.
[0045] Preferably, the chromatographic column is a SHISEIDO CAPCELL PAK MGⅢC18 chromatographic column with a specification of 5 μm and 250 mm×4.6 mm.
[0046] Preferably, the volume fraction of the phosphoric acid solution is 0.3%.
[0047] Preferably, the column temperature of the chromatographic column is 28-32°C.
[0048] More preferably, the column temperature of the chromatographic column is 30°C.
[0049] Preferably, the flow rate of the gradient elution is 0.8-1.2 mL / min.
[0050] More preferably, the flow rate of the gradient elution is 1 mL / min.
[0051] Application of any of the above-mentioned pretreatment methods and / or high performance liquid chromatography analysis methods in establishing HPLC fingerprints of corn silk broken wall slices and / or quality control of corn silk broken wall slices.
[0052] A method for constructing an HPLC fingerprint of corn silk broken wall slices, comprising the steps of using any of the above-mentioned high performance liquid chromatography analysis methods to detect different batches of corn silk broken wall slice samples, recording the chromatograms, importing the chromatograms into a traditional Chinese medicine chromatographic fingerprint similarity evaluation system, screening and confirming common peaks, and obtaining the HPLC fingerprint of corn silk broken wall slices.
[0053] The HPLC fingerprint of the corn silk broken wall slices contains 18 fingerprint peaks, with peak 5 as the S peak, and the specified values of the relative retention time are:
[0054] Peak No. 1 is 0.441, Peak No. 2 is 0.624, Peak No. 3 is 0.689, Peak No. 4 is 0.956, Peak No. 5 is 1.000, Peak No. 6 is 1.129, Peak No. 7 is 1.216, Peak No. 8 is 1.451, Peak No. 9 is 1.519, Peak No. 10 is 1.672, Peak No. 11 is 2.549, Peak No. 12 is 2.642, Peak No. 13 is 2.918, Peak No. 14 is 3.445, Peak No. 15 is 4.125, Peak No. 16 is 4.161, Peak No. 17 is 4.188, and Peak No. 18 is 4.257.
[0055] The different batches are no less than 15 batches.
[0056] A quality detection method for corn silk broken wall pieces, comprising the following steps:
[0057] S1. Take the sample of corn silk broken wall slices to be tested, use any of the above-mentioned high performance liquid chromatography analysis methods for detection, record the chromatogram, and obtain the HPLC spectrum of the sample of corn silk broken wall slices to be tested;
[0058] S2. The HPLC fingerprint of the above-mentioned corn silk broken wall slices and the HPLC fingerprint of the corn silk broken wall slice sample to be tested are introduced into the Chinese medicine chromatographic fingerprint similarity evaluation system for comparison. The following two conditions are met to determine the qualification:
[0059] The HPLC spectrum of the corn silk broken wall slice sample to be tested presents a fingerprint peak whose relative retention time is within ±10% of the specified value in the HPLC fingerprint spectrum of the corn silk broken wall slice;
[0060] The similarity between the HPLC spectrum of the corn silk broken wall slice sample to be tested and the HPLC fingerprint spectrum of the corn silk broken wall slice is calculated, and the similarity between the HPLC spectrum of the corn silk broken wall slice sample to be tested and the HPLC fingerprint spectrum of the corn silk broken wall slice is not less than 0.85;
[0061] The HPLC fingerprint of the corn silk broken wall slices contains 18 fingerprint peaks, with peak 5 as the S peak, and the specified values of the relative retention time are:
[0062] Peak No. 1 is 0.441, Peak No. 2 is 0.624, Peak No. 3 is 0.689, Peak No. 4 is 0.956, Peak No. 5 is 1.000, Peak No. 6 is 1.129, Peak No. 7 is 1.216, Peak No. 8 is 1.451, Peak No. 9 is 1.519, Peak No. 10 is 1.672, Peak No. 11 is 2.549, Peak No. 12 is 2.642, Peak No. 13 is 2.918, Peak No. 14 is 3.445, Peak No. 15 is 4.125, Peak No. 16 is 4.161, Peak No. 17 is 4.188, and Peak No. 18 is 4.257.
[0063] Compared with the prior art, the present invention has the following beneficial effects:
[0064] The present invention discloses an HPLC fingerprint of corn silk broken wall slices and a construction method and application thereof. Using the method of the present invention, 18 common fingerprint peaks can be determined, and at the same time, the separation between the peaks is good, the peak distribution is uniform, and the baseline is stable. The methodological investigation results show that the method of the present invention has good specificity and good repeatability, stability and durability. The method of the present invention can more objectively and comprehensively evaluate the overall quality of corn silk broken wall slices, laying a foundation for the quality control of corn silk broken wall slices. BRIEF DESCRIPTION OF THE DRAWINGS
[0065] Figure 1 The effect of different extraction solvents on the chromatogram of the test sample.
[0066] Figure 2The effects of different extraction methods on the chromatograms of the test samples.
[0067] Figure 3 The effect of different extraction material-liquid ratios on the chromatogram of the test sample.
[0068] Figure 4 The effect of different extraction times on the chromatogram of the test sample.
[0069] Figure 5 The effects of different extraction methods on the chromatograms of the test samples.
[0070] Figure 6 The effect of different extraction times on the chromatogram of the test sample.
[0071] Figure 7 It is the isotropic absorption diagram of the test solution and the chromatogram at 273nm.
[0072] Figure 8 The influence of different mobile phase systems on the chromatogram of the test sample.
[0073] Fig. 9 The effect of different elution gradients on the chromatogram of the test sample.
[0074] Fig.10 The effect of different elution flow rates on the chromatogram of the test sample.
[0075] Fig.11 The effect of different column temperatures on the chromatogram of the test sample.
[0076] Fig.12 The effect of different injection volumes on the chromatogram of the test sample.
[0077] Fig.13 A new reference atlas generated for the analysis of 20 batches of corn silk broken wall slices.
[0078] Fig.14 This is the HPLC reference fingerprint of corn silk broken wall slices.
[0079] Fig.15 This is the identification diagram of the reference peak (Peak 5) of the test sample.
[0080] Fig.16 For exclusive results.
[0081] Fig.17 This is the instrument precision result.
[0082] Fig.18 For reproducible results.
[0083] Fig.19 The stability result.
[0084] Fig. 20The durability results of different chromatographic columns are shown in Figure 2.
[0085] Fig.21 Durability results for different instruments.
[0086] Fig. 22 The chromatogram result is the comparative example 1.
[0087] Fig.23 The chromatogram result is the comparative example 2.
[0088] Fig.24 The chromatogram result is the comparative example 3. DETAILED DESCRIPTION
[0089] The present invention is further described below with reference to specific examples, but the examples do not limit the present invention in any form. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.
[0090] Unless otherwise specified, the reagents and materials used in the following examples are commercially available.
[0091] Reference substance information used in the examples of the present invention: Ferulic acid, batch number 110773-201915, content 99.4%, purchased from China Food and Drug Inspection Institutes.
[0092] Information on the test samples used in the embodiments of the present invention: The pilot samples of corn silk broken wall slices were provided by Zhongshan Zhongzhi Chinese Medicine Slices Co., Ltd., which met the quality standard requirements of “Research Specifications for Quality Standards of Traditional Chinese Medicine Broken Wall Slices in Guangdong Province (Trial)”, and the batch numbers were 2203010A, 2203020A, 2203030A, 2203040A, 2203050A, 20220401, 20220402, 20220403, 20220404, 20220406, 20220407, 20220408, 20220410, 20220412, 20220413, 20220414, 20220415, 20220416, 20220417, and 20220418, respectively.
[0093] Example 1 Effect of the test sample preparation method on the HPLC fingerprint of corn silk broken wall slices
[0094] 1. Extraction solvent
[0095] 1. Experimental Methods
[0096] Preparation of test sample: Take 2g of corn silk broken wall slices, accurately weigh 5 portions, put them in a stoppered conical flask, accurately add 25mL of methanol, 30% methanol aqueous solution (v / v), 50% methanol aqueous solution (v / v), 70% methanol aqueous solution (v / v) and ethanol respectively, weigh the weight, extract by ultrasonic for 30min (power 560W, frequency 40KHz), take out and cool, make up the weight with extraction solvent, filter with 0.45μm microporous filter membrane, and take the filtrate to obtain the product.
[0097] Chromatographic conditions: using a SHISEIDO CAPCELL PAK MGⅢC18 chromatographic column (5μm, 250mm×4.6mm), acetonitrile as mobile phase A, 0.1% phosphoric acid aqueous solution (v / v) as mobile phase B; flow rate 1.0mL / min; column temperature 30°C; detection wavelength 273nm; sample injection volume 10μL, gradient elution conditions: 0min~10min~20min~55min~60min~85min~90min, the change of mobile phase A is 3%~5%~20%~50%~70%~95%~3%.
[0098] 2. Experimental results
[0099] The results are as follows Figure 1 As shown in the figure, the number of peaks obtained with each extraction solvent is basically the same, and the types of component peaks obtained are consistent, but the response value of the main component peak obtained by methanol extraction is significantly higher than that of ethanol. There are relatively few interfering small peaks in the methanol extracted sample, and the baseline is stable. Therefore, pure methanol is selected as the extraction solvent for corn wall broken slices.
[0100] 2. Extraction method
[0101] 1. Experimental Methods
[0102] Preparation of test sample: Take 2 g of corn silk broken wall slices, accurately weigh 2 portions, put in a stoppered conical flask, accurately add 25 mL of methanol, weigh the weight, heat reflux extraction for 30 min and ultrasonic treatment for 30 min (power 560 W, frequency 40 kHz), cool, weigh again, make up the lost weight with methanol, shake well, filter, and take the filtrate.
[0103] The chromatographic conditions were in accordance with those in “I. Extraction solvent”.
[0104] 2. Experimental results
[0105] The results are as follows Figure 2 As shown in the figure, the number of peaks in the chromatograms of the test samples obtained by the two extraction methods is basically the same, the types of main peaks are the same, the chromatographic peak area in the chromatogram of the sample obtained by reflux extraction is slightly larger than that of the ultrasonic extraction sample, and there are no other significant differences. In view of the convenience of ultrasonic extraction operation, ultrasonic extraction was selected as the extraction method for corn silk broken wall slices.
[0106] 3. Extraction material-liquid ratio
[0107] 1. Experimental Methods
[0108] Preparation of test sample: Take 1 portion of 1g (No. 1) and 4 portions of 2g (No. 2-5) of corn silk broken wall slices, weigh accurately, put in a stoppered conical flask, accurately add 10mL of methanol to No. 1 and No. 2, accurately add 15mL of methanol to No. 3 and No. 4, accurately add 25mL of methanol to No. 5 and weigh the weight, ultrasonically extract for 30min (power 560W, frequency 40KHz), cool after taking out, make up with methanol, filter No. 1-3 with a 0.45μm microporous membrane, take the filtrate, and get the test solution 1-3;
[0109] Filter No. 4 and No. 5, evaporate the filtrate, dissolve the residue in methanol to make up to 2 mL, filter with a 0.45 μm microporous membrane, and take the filtrate to obtain the test solution 4-5.
[0110] The chromatographic conditions were in accordance with those in “I. Extraction solvent”.
[0111] 2. Experimental results
[0112] The results are as follows Figure 3 As shown, the five components of the test solution were fully extracted, and the peak response values of the main components were relatively uniform. Therefore, 2 g of sample was added with 25 mL of methanol for extraction for 30 min, and the filtrate was evaporated to dryness and the methanol was diluted to 2 mL as the extraction material-liquid ratio for the preparation of the test solution.
[0113] 4. Extraction time
[0114] 1. Experimental Methods
[0115] Preparation of test sample: Take 2g of corn silk broken wall slices, accurately weigh 5 portions, put them in stoppered conical flasks, accurately add 25mL of methanol to each portion, weigh the weight, and ultrasonically extract for 30, 45, 60, 90, and 120min (power 560W, frequency 40KHz), cool after taking out, make up with methanol, filter, evaporate the filtrate, dissolve the residue with methanol to 2mL, filter with 0.45μm microporous filter membrane, and take the filtrate.
[0116] The chromatographic conditions were in accordance with those in “I. Extraction solvent”.
[0117] 2. Experimental results
[0118] The results are as follows Figure 4 As shown, with the extension of extraction time, the extraction efficiency is slightly different (the peak area of the main component peak is slightly increased). Considering the time saving and extraction efficiency, 30 min of extraction was finally selected as the extraction time for the preparation of the test solution.
[0119] 5. Extraction method
[0120] 1. Experimental Methods
[0121] Preparation of the test sample: Take 2g of corn silk broken wall slices, accurately weigh 2 portions, place in stoppered conical bottles, accurately add 25mL of methanol, weigh the weight, ultrasonically extract for 30min (power 560W, frequency 40KHz), cool after taking out, add methanol to make up, filter, evaporate the filtrate No. 1 to dryness, dissolve the residue with methanol to 2mL, filter with 0.45μm microporous membrane, and take the filtrate to obtain;
[0122] Filtrate No. 2 was evaporated to dryness, the residue was dissolved in 15 mL of water, extracted twice with ethyl acetate, 15 mL each time, the ethyl acetate layers were combined, evaporated to dryness, the residue was dissolved in methanol to make the volume 2 mL, filtered with a 0.45 μm microporous filter membrane, and the filtrate was taken to obtain the product.
[0123] The chromatographic conditions were in accordance with those in “I. Extraction solvent”.
[0124] 2. Experimental results
[0125] The results are as follows Figure 5 As shown in the figure, the number of peaks obtained by each extraction solvent is not much different, and the types of component peaks obtained are basically the same, but the response value of the main component peak obtained by ethyl acetate extraction is significantly higher than that of methanol extraction, and there are relatively few interfering small peaks in the ethyl acetate extraction sample, and the baseline is stable. Therefore, methanol extraction followed by water dissolution and then ethyl acetate extraction are selected as the extraction method for corn silk broken wall slices.
[0126] 6. Extraction times
[0127] 1. Experimental Methods
[0128] Preparation of the test sample: Take 2g of corn silk broken wall slices, accurately weigh 3 portions, place in stoppered conical bottles, accurately add 25mL of methanol, weigh the weight, ultrasonically extract for 30min (power 560W, frequency 40KHz), cool after taking out, add methanol to make up the weight, filter, and evaporate the filtrate. Dissolve the residue with 15mL of water, extract No. 1 once with ethyl acetate, No. 2 twice with ethyl acetate, and No. 3 three times with ethyl acetate, each time 15mL, combine the ethyl acetate layers, evaporate to dryness, dissolve the residue with methanol to 2mL, filter with a 0.45μm microporous filter membrane, and take the filtrate to obtain.
[0129] The chromatographic conditions were in accordance with those in “I. Extraction solvent”.
[0130] 2. Experimental results
[0131] The results are as follows Figure 6As shown: With the increase of extraction times, the extraction efficiency is slightly different (the peak area of the main component peak is slightly increased). Considering the saving of reagents and extraction efficiency, two extractions were finally selected as the number of extractions for the preparation of the test solution.
[0132] Example 2 A pre-treatment method for HPLC fingerprint of corn silk broken wall slices
[0133] Take 2g of corn silk broken wall slices, accurately weigh, place in a stoppered conical flask, accurately add 25mL of methanol, weigh, ultrasonic for 30min, cool to room temperature, make up with methanol, shake well, filter, evaporate the filtrate to dryness, dissolve the residue with 15mL of water, extract twice with ethyl acetate, 15mL each time, combine the ethyl acetate layers, evaporate to dryness, dissolve the residue with methanol to make up to 2mL, filter with a 0.45μm microporous filter membrane, and take the filtrate to obtain.
[0134] Example 3 Effect of Chromatographic Conditions on HPLC Fingerprint of Corn Silk Broken Wall Pieces
[0135] 1. Detection wavelength
[0136] 1. Experimental Methods
[0137] The corn silk broken wall slices test solution was prepared according to the pretreatment method of Example 2.
[0138] The test solution is scanned at full wavelength, and the best detection wavelength is selected from its isolinear absorption diagram. The evaluation indicators are: large analytical signal response value at this wavelength, high peak information, uniform peak distribution and stable baseline, and good peak separation.
[0139] 2. Experimental results
[0140] The results are as follows Figure 7 As shown, the sample peak at 273nm has more complete information and a larger response value, so 273nm is selected as the detection wavelength.
[0141] 2. Mobile Phase System
[0142] 1. Experimental Methods
[0143] The corn silk broken wall slices test solution was prepared according to the pretreatment method of Example 2.
[0144] The chromatographic conditions were in accordance with "I. Extraction solvent" in Example 1, except that the mobile phase systems were set to: acetonitrile-0.1% acetic acid aqueous solution (v / v) (S1); acetonitrile-0.1% formic acid aqueous solution (v / v) (S2); acetonitrile-0.3% phosphoric acid aqueous solution (v / v) (S3); methanol-0.3% phosphoric acid aqueous solution (v / v) (S4); methanol-water (S5); acetonitrile-water (S6), with the selection criteria being a large number of peaks in the sample spectrum, uniform peak distribution, good peak shape and main component peak separation effect, and a stable baseline.
[0145] 2. Experimental results
[0146] The results are as follows Figure 8 As shown, the mobile phase acetonitrile-0.3% phosphoric acid aqueous solution (v / v) obtained the test sample has more peak information, a more stable baseline, and better separation and peak shape, so the mobile phase system was finally determined to be acetonitrile-0.3% phosphoric acid aqueous solution (v / v).
[0147] 3. Elution Gradient
[0148] 1. Experimental Methods
[0149] The corn silk broken wall slices test solution was prepared according to the pretreatment method of Example 2.
[0150] Chromatographic conditions: SHISEIDO CAPCELL PAK MGⅢC18 column (5μm, 250mm×4.6mm) was used; flow rate was 1.0mL / min; column temperature was 25°C; detection wavelength was 273nm; sample injection volume was 10μL; acetonitrile was used as mobile phase A, and 0.3% phosphoric acid aqueous solution was used as mobile phase B. Elution was performed according to the elution gradient shown in Table 1, and the selection criteria were stable baseline of the sample spectrum, a large number of peaks, uniform peak distribution, and high separation of the main component peaks.
[0151] Table 1 Mobile phase elution gradient
[0152]
[0153] 2. Experimental results
[0154] The results are as follows Fig. 9 As shown, the number of peaks in each gradient is basically the same, but the baseline of gradient 12 is stable, the peak distribution is uniform, and the main component peak separation effect is good, so gradient 12 is selected as the elution gradient.
[0155] 4. Mobile phase elution flow rate
[0156] 1. Experimental Methods
[0157] The corn silk broken wall slices test solution was prepared according to the pretreatment method of Example 2.
[0158] Chromatographic conditions: use SHISEIDO CAPCELL PAK MGⅢC18 chromatographic column (5μm, 250mm×4.6mm); column temperature 30℃; detection wavelength 273nm; sample injection volume 10μL; acetonitrile as mobile phase A, 0.3% phosphoric acid aqueous solution (v / v) as mobile phase B, elution with gradient 12 in "III. Elution gradient", and set the flow rates to 0.8, 0.9, 1.0, 1.1, and 1.2mL / min, respectively.
[0159] 2. Experimental results
[0160] The results are as follows Fig.10 As shown in the figure, the effect of flow rate on elution effect is not very significant. When the flow rate is 1.0 mL / min, the separation, symmetry and peak shape are good and the elution time is moderate. Therefore, 1.0 mL / min is selected as the elution flow rate.
[0161] 5. Column temperature
[0162] 1. Experimental Methods
[0163] The corn silk broken wall slices test solution was prepared according to the pretreatment method of Example 2.
[0164] Chromatographic conditions: use SHISEIDO CAPCELL PAK MGⅢC18 chromatographic column (5μm, 250mm×4.6mm); flow rate 1.0mL / min; detection wavelength 273nm; sample injection volume 10μL; acetonitrile as mobile phase A, 0.3% phosphoric acid aqueous solution (v / v) as mobile phase B, elution with gradient 12 in "III. Elution gradient", and set the column temperature to 20, 25, 30, 35 and 40°C, respectively.
[0165] 2. Experimental results
[0166] The results are as follows Fig.11 As shown, at 30°C, the separation and peak shape of the chromatographic peaks are better and the elution time is moderate, so a column temperature of 30°C is used as the elution column temperature.
[0167] 6. Injection Volume
[0168] 1. Experimental Methods
[0169] The corn silk broken wall slices test solution was prepared according to the pretreatment method of Example 2.
[0170] Chromatographic conditions: use SHISEIDO CAPCELL PAK MGⅢC18 chromatographic column (5μm, 250mm×4.6mm); flow rate 1.0mL / min; column temperature 30℃; detection wavelength 273nm; acetonitrile as mobile phase A, 0.3% phosphoric acid aqueous solution (v / v) as mobile phase B, elution with gradient 12 in "III. Elution gradient", and set the injection volume to 5, 10, 15, 20 and 25μL respectively.
[0171] 2. Experimental results
[0172] The results are as follows Fig.12 As shown in the figure, the separation and peak shape of the chromatographic peaks are good and the elution time is moderate under the injection volume of 10 μL, so the injection volume of 10 μL is used as the elution injection volume.
[0173] Example 4 A method for constructing an HPLC fingerprint of corn silk broken wall slices
[0174] 1. Preparation of reference solution
[0175] Take an appropriate amount of ferulic acid reference substance, weigh it accurately, and add methanol to prepare a reference substance solution containing 250.0 μg of ferulic acid per 1 mL.
[0176] 2. Preparation of test solution
[0177] Take 2 g of broken wall slices of corn silk from 20 batches respectively, weigh accurately, put them in a stoppered conical flask, accurately add 25 mL of methanol, weigh, ultrasonicate for 30 min, cool to room temperature, make up with methanol, shake well, filter, evaporate the filtrate to dryness, dissolve the residue with 15 mL of water, extract twice with ethyl acetate, 15 mL each time, combine the ethyl acetate layers, evaporate to dryness, dissolve the residue with methanol to make up to 2 mL, filter with a 0.45 μm microporous filter membrane, and take the filtrate to obtain.
[0178] 3. Chromatographic conditions and system suitability
[0179] Octadecylsilane bonded silica gel was used as filler (5 μm, 250 mm×4.6 mm); acetonitrile was used as mobile phase A, 0.3% phosphoric acid aqueous solution (v / v) was used as mobile phase B, and gradient elution was performed according to the conditions in Table 2; the detection wavelength was 273 nm; the column temperature was 30° C.; the flow rate was 1.0 mL / min. The theoretical plate number calculated based on ferulic acid should not be less than 10,000.
[0180] Table 2 Mobile phase elution gradient
[0181] Time (min) Mobile phase A (%) Mobile phase B (%) 0~8 10→19 90→81 8~13 19→19 81→81 13~55 19→45 81→55 55~65 45→68 55→32 65~80 68→68 32→32 80~85 68→10 32→90
[0182] 4. Assay
[0183] Accurately pipette 10 μL of reference solution and test solution, inject into liquid chromatograph, measure, and record chromatogram. Use the "Chinese Medicine Chromatographic Fingerprint Similarity Evaluation System (2012 Edition)" of the National Pharmacopoeia Committee to generate a reference spectrum (average method), screen and confirm the common peaks, and generate the HPLC fingerprint of corn silk broken wall slices through software.
[0184] 5. Chromatographic peak identification and reference peak selection
[0185] A total of 18 chromatographic peaks were identified as the common fingerprint peaks of corn silk broken wall slices ( Fig.13 and Fig.14 ), among which Peak 5 has a good separation effect, and its peak position and peak height are in the middle, so Peak 5 is determined as the reference peak (S peak). The retention time and DAD spectrum of the ferulic acid reference peak correspond one-to-one with Peak 5 in the test sample and the reference spectrum ( Fig.15 ), so peak 5 was determined to be ferulic acid.
[0186] The similarity analysis (selecting the time window of 0.1) and the relative retention time of the common peaks were performed on the spectra of 20 batches of samples and the generated reference spectra using the software "Similarity Evaluation System of Chromatographic Fingerprint of Traditional Chinese Medicine (2012 Edition)" of the National Pharmacopoeia Committee, as shown in Tables 3 and 4. The results showed that the similarity between the spectra of 20 batches of samples and the reference spectra was greater than 0.887. Considering that the raw medicinal materials of broken wall slices will be affected by the climate such as temperature and rainfall during the planting process in the ecological planting base, resulting in certain batch differences, the proposed limit is 0.85, that is, "according to the Similarity Evaluation System of Chromatographic Fingerprint of Traditional Chinese Medicine, the similarity between the fingerprint of the test sample and the reference fingerprint shall not be less than 0.85 after similarity calculation".
[0187] Table 3 Similarity of fingerprints of 20 batches of corn silk broken wall slices
[0188]
[0189]
[0190] Table 4 Relative retention time of common peaks in fingerprint of corn silk broken wall slices
[0191]
[0192] Taking peak 5 as the reference peak (S peak), the relative retention times of characteristic peaks 1 to 18 are within ±10% of the specified values; the specified values are peak 1 0.441, peak 2 0.624, peak 3 0.689, peak 4 0.956, peak 5 1.000, peak 6 1.129, peak 7 1.216, peak 8 1.451, peak 9 1.519, peak 10 1.672, peak 11 2.549, peak 12 2.642, peak 13 2.918, peak 14 3.445, peak 15 4.125, peak 16 4.161, peak 17 4.188, and peak 18 4.257.
[0193] Example 5 Methodological Investigation
[0194] 1. Exclusiveness Investigation
[0195] 1. Experimental Methods
[0196] Take corn silk broken wall slices with batch number 2203010A, prepare test solution and blank test solution according to the method of Example 4, inject, analyze according to the chromatographic conditions of Example 4, and record the chromatogram.
[0197] 2. Experimental results
[0198] The results are as follows Fig.16 As shown, the dissolving solvent and eluting solvent used to prepare the test sample have basically no absorption under the chromatographic conditions and have no interference with the chromatographic analysis of the test sample, indicating that the established method has good specificity.
[0199] 2. Instrument Precision Inspection
[0200] 1. Experimental Methods
[0201] The corn silk broken wall pieces with batch number 2203010A were taken and prepared into a test solution according to the method of Example 4, and the sample was injected 6 times continuously, analyzed according to the chromatographic conditions of Example 4, and the chromatogram was recorded. The Chinese Pharmacopoeia Committee's "Chinese Medicine Chromatographic Fingerprint Similarity Evaluation System" (2012 Edition) was used to analyze the data of the 6 obtained spectra.
[0202] 2. Experimental results
[0203] The results are shown in Tables 5 to 7 and Fig.17 As shown: the similarity of the whole spectrum of the 6 spectra reached 1.000, the RSD values of the relative retention time of the 18 main component peaks were all less than 0.133%, and the RSD values of the relative peak area were all less than 1.812%. The inspection results showed that the precision of the instrument met the requirements.
[0204] Table 5 Similarity of spectra in the instrument precision study
[0205] Precision 1 Precision 2 Precision 3 Precision 4 Precision 5 Precision 6 Precision 1 1.000 1.000 1.000 1.000 1.000 1.000 Precision 2 1.000 1.000 1.000 1.000 1.000 1.000 Precision 3 1.000 1.000 1.000 1.000 1.000 1.000 Precision 4 1.000 1.000 1.000 1.000 1.000 1.000 Precision 5 1.000 1.000 1.000 1.000 1.000 1.000 Precision 6 1.000 1.000 1.000 1.000 1.000 1.000
[0206] Table 6 Relative retention time of the spectrum of instrument precision investigation
[0207]
[0208]
[0209] Table 7 Relative peak area of instrument precision inspection spectrum
[0210]
[0211] 3. Repeatability Study
[0212] 1. Experimental Methods
[0213] Six portions of corn silk broken wall slices with batch number 2203010A were taken and prepared into test solutions according to the method of Example 4, respectively, and analyzed according to the chromatographic conditions of Example 4, and the chromatograms were recorded. The Chinese Pharmacopoeia Committee's "Chinese Medicine Chromatographic Fingerprint Similarity Evaluation System" (2012 Edition) was used to perform data analysis on the six obtained spectra.
[0214] 2. Experimental results
[0215] The results are shown in Tables 8 to 10 and Fig.18 As shown in the figure, the similarity of the whole spectrum of the six spectra reached 0.999, the RSD values of the relative retention time of the 18 main component peaks were all less than 0.327%, and the RSD values of the relative peak area were all less than 2.866%. The results of the investigation showed that the repeatability of the method met the requirements.
[0216] Table 8 Similarity of reproducibility test spectra
[0217] Repeatability 1 Repeatability 2 Repeatability 3 Repeatability 4 Repeatability 5 Repeatability 6 Repeatability 1 1.000 1.000 0.999 0.999 0.999 1.000 Repeatability 2 1.000 1.000 0.999 0.999 0.999 1.000 Repeatability 3 0.999 0.999 1.000 1.000 1.000 1.000 Repeatability 4 0.999 0.999 1.000 1.000 1.000 0.999 Repeatability 5 0.999 0.999 1.000 1.000 1.000 0.999 Repeatability 6 1.000 1.000 1.000 0.999 0.999 1.000
[0218] Table 9 Relative retention time of repeatability test spectra
[0219]
[0220] Table 10 Relative peak area of repeatability test spectrum
[0221]
[0222] 4. Stability inspection
[0223] 1. Experimental Methods
[0224] The corn silk broken wall pieces with batch number 2203010A were taken and prepared into a test solution according to the method of Example 4. The samples were injected at 0, 2, 4, 8, 12, and 24 hours after preparation, and the chromatograms were analyzed according to the chromatographic conditions of Example 4. The chromatograms were recorded. The Chinese Pharmacopoeia Committee's "Chinese Medicine Chromatographic Fingerprint Similarity Evaluation System" (2012 Edition) was used to analyze the data of the 6 obtained spectra.
[0225] 2. Experimental results
[0226] The results are shown in Tables 11 to 13 and Fig.19 As shown: the full spectrum similarity of the 6 spectra is above 0.999, the RSD values of the relative retention time of the 18 main component peaks are all less than 0.180%, and the RSD values of the relative peak area are all less than 1.887%. The results show that the sample has good stability within 24 hours and meets the methodological requirements.
[0227] Table 11 Similarity of stability test spectra
[0228] 0h 2h 4h 8h 12h 24h 0h 1.000 1.000 1.000 1.000 1.000 0.999 2h 1.000 1.000 1.000 1.000 1.000 1.000 4h 1.000 1.000 1.000 1.000 1.000 1.000 8h 1.000 1.000 1.000 1.000 1.000 1.000 12h 1.000 1.000 1.000 1.000 1.000 1.000 24h 0.999 1.000 1.000 1.000 1.000 1.000
[0229] Table 12 Relative retention time of stability test spectrum
[0230]
[0231] Table 13 Relative peak areas of stability test spectra
[0232]
[0233]
[0234] 5. Durability
[0235] 1. Different chromatographic columns
[0236] (1) Experimental methods
[0237] Corn silk broken wall pieces with batch number 2203010A were taken and prepared into test solution according to the method of Example 4, respectively using Kromasil 100-5-C18 (5 μm, 250 mm×4.6 mm), YMC Triart C18 (5 μm, 250 mm×4.6 mm), Four different types of chromatographic columns, T3 C18 (5 μm, 250 mm × 4.6 mm) and Shiseido CAPCell PAK C18 MGⅢ (5 μm, 250 mm × 4.6 mm), were used for analysis and recording of chromatograms according to the chromatographic conditions of Example 4. The 4 obtained chromatograms were analyzed using the Chinese Pharmacopoeia Committee's "Chinese Medicine Chromatographic Fingerprint Similarity Evaluation System" (2012 Edition).
[0238] (2) Experimental results
[0239] The results are shown in Table 14 and Fig. 20 As shown in the figure: the similarity of the whole spectrum of the four spectra is above 0.991, indicating that this method is basically applicable to different chromatographic columns. However, the results of the investigation suggest that different chromatographic columns can be used for analysis. Figure 1 However, the RSD values of the relative retention times of the 18 main component peaks are quite different, so there are still certain differences in the retention time, peak area and separation of the main chromatographic peaks. It is recommended to use the same brand and model of chromatographic columns when analyzing samples by fingerprint analysis to reduce the error in sample quality evaluation caused by chromatographic column differences.
[0240] Table 14 Similarity of spectra of different chromatographic columns
[0241]
[0242] 2. Different instruments
[0243] (1) Experimental methods
[0244] The corn silk broken wall slices with batch number 2203010A were taken and prepared into a test solution according to the method of Example 4. The solution was analyzed and recorded on Waters 2695 / 2998, Agilent 1260Ⅱ and Thermo U3000 liquid chromatographs using Shiseido CAPCell PAK C18 MGⅢ (250 mm×4.6 mm, 5 μm) chromatographic columns according to the chromatographic conditions of Example 4. The chromatograms were analyzed using the "Chinese Medicine Chromatographic Fingerprint Similarity Evaluation System" (2012 Edition) of the National Pharmacopoeia Committee for data analysis of the three obtained spectra.
[0245] (2) Experimental results
[0246] The results are shown in Table 15 and Fig.21 As shown in the figure: the similarity of the full spectrum of the three spectra is 0.998, which meets the methodological requirements. However, it can be seen from the spectra that different instrument analyses, although the overall chromatogram Figure 1 However, there are still some differences in the separation of the main chromatographic peaks. It is recommended to use the same liquid chromatograph when analyzing samples by fingerprint to reduce the error in sample quality evaluation caused by instrument differences.
[0247] Table 15 Similarity of spectra investigated by different instruments
[0248] Spectrum Agilent 1260Ⅱ Thermo U3000 Waters2695 / 2998 Agilent 1260Ⅱ 1.000 0.999 0.998 Thermo U3000 0.999 1.000 0.999 Waters2695 / 2998 0.998 0.999 1.000
[0249] Comparative Example 1
[0250] 1. Experimental Methods
[0251] Preparation of test solution: Take corn silk broken wall pieces and prepare according to the test sample preparation method in "HPLC fingerprint of corn silk" by Xie Caixia et al. (published on May 5, 2015). The specific experimental steps are as follows:
[0252] Accurately weigh 6.0 g of corn silk broken wall slices, add 180 mL of 60% ethanol aqueous solution (v / v), reflux at 80°C for 2 h, filter, evaporate the supernatant in a water bath, dissolve it in methanol and make up to volume in a 10 mL volumetric flask, ultrasonicate for 30 min, and filter through a 0.45 μm microporous filter membrane.
[0253] The chromatographic conditions were according to Example 4.
[0254] 2. Experimental Results
[0255] The results are as follows Fig. 22 As shown, the interference peaks in the early stage of the chromatogram obtained by the chromatographic conditions of the present invention are smaller than those in the comparative file 1, the baseline is relatively flat, and the peak shape is better.
[0256] Comparative Example 2
[0257] 1. Experimental Methods
[0258] The corn silk broken wall slices test solution was prepared according to the method of Example 4.
[0259] Chromatographic conditions: The elution was performed according to the chromatographic conditions in "HPLC Fingerprint of Corn Silk" by Xie Caixia et al. (published on May 5, 2015). The specific experimental steps are as follows:
[0260] An Agilent ZORBAX SB-C column (4.6 mm × 250 mm, 5 μm) was used, with a detection wavelength of 273 nm, a column temperature of 30°C, an injection volume of 10 μL, a flow rate of 0.8 mL / min, methanol as mobile phase A, and 0.2% phosphoric acid aqueous solution (v / v) as mobile phase B. The gradient elution conditions were: 0-45 min, 10%-40% A, 45-85 min, 40%-60% A, 85-100 min, 60%-70% A.
[0261] 2. Experimental Results
[0262] The results are as follows Fig.23 As shown, there is no interference from other peaks in the early stage, the baseline is relatively flat, and the peak shape is symmetrical. However, the separation of some peaks in the second half of the chromatogram is not ideal, and the detection and analysis takes a long time.
[0263] Comparative Example 3
[0264] 1. Experimental Methods
[0265] Take corn silk broken wall pieces, and conduct the experiment according to the test sample preparation method and chromatographic conditions in "HPLC fingerprint of corn silk" by Xie Caixia et al. (publication date: May 5, 2015). The specific experimental steps are as follows:
[0266] Accurately weigh 6.0 g of corn silk broken wall slices, add 180 mL of 60% ethanol aqueous solution (v / v), reflux at 80°C for 2 h, filter, evaporate the supernatant in a water bath, dissolve it in methanol and make up to volume in a 10 mL volumetric flask, ultrasonicate for 30 min, and filter through a 0.45 μm microporous filter membrane.
[0267] An Agilent ZORBAX SB-C column (4.6 mm × 250 mm, 5 μm) was used, with a detection wavelength of 273 nm, a column temperature of 30°C, an injection volume of 10 μL, a flow rate of 0.8 mL / min, methanol as mobile phase A, and 0.2% phosphoric acid aqueous solution (v / v) as mobile phase B. The gradient elution conditions were: 0-45 min, 10%-40% A, 45-85 min, 40%-60% A, 85-100 min, 60%-70% A.
[0268] 2. Experimental Results
[0269] The results are as follows Fig.24 As shown, this method has low chromatographic peak response, large early solvent peaks and many impurity peaks, few common peaks, long detection time, and poor display effect of the entire spectrum.
[0270] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A pretreatment method for detecting corn silk broken wall pieces by high performance liquid chromatography, characterized in that: The following steps are involved: S1. Mix the sample to be tested with methanol and perform ultrasound, cool it, use methanol to make up for the weight loss, separate the solid and liquid, and remove the methanol in the liquid; S2. dissolving the product of step S1 in water, adding ethyl acetate for extraction, taking the ethyl acetate layer and removing the ethyl acetate to obtain a residue; S3. Dissolve the residue in methanol, filter with a microporous membrane, and take the filtrate.
2. The pre-treatment method according to claim 1, characterized in that: In step S1, the mass volume ratio of the sample to be tested to methanol is 1 g: (12-13) mL.
3. The pre-treatment method according to claim 1, characterized in that: In step S1, the ultrasonication time is 25 to 35 minutes.
4. The pre-treatment method according to claim 1, characterized in that: In step S2, the extraction is performed 2 to 3 times.
5. A high performance liquid chromatography analysis method, characterized in that: The following steps are involved: Reference solution: ferulic acid solution; Test solution: prepared by the pretreatment method described in any one of claims 1 to 4; Chromatographic conditions: Octadecylsilane bonded silica gel is used as the filler of the chromatographic column, acetonitrile is used as the mobile phase A, and a phosphoric acid solution with a volume fraction of 0.28-0.32% is used as the mobile phase B. In the gradient elution program, the volume percentage of mobile phase A in the mobile phase system changes as follows: From 0 to 8 min, mobile phase A increased from 10% to 19%; 8-13 min, mobile phase A is 19%; From 13 to 55 min, mobile phase A increased from 19% to 45%; From 55 to 65 min, mobile phase A increased from 45% to 68%; 65-80 min, mobile phase A is 68%; At 80-85 min, mobile phase A was reduced from 68% to 10%; The detection wavelength is 273 nm, and the theoretical plate number calculated based on ferulic acid should be no less than 10,000.
6. The high performance liquid chromatography analysis method according to claim 5, characterized in that: The column temperature of the chromatographic column is 28-32°C.
7. The high performance liquid chromatography analysis method according to claim 5, characterized in that: The flow rate of the gradient elution is 0.8-1.2 mL / min.
8. Application of the pretreatment method described in any one of claims 1 to 4 and / or the high performance liquid chromatography analysis method described in any one of claims 5 to 7 in establishing the HPLC fingerprint of corn silk broken wall slices and / or in quality control of corn silk broken wall slices.
9. A method for constructing HPLC fingerprint of corn silk broken wall slices, characterized in that: Use the high performance liquid chromatography analysis method described in any one of claims 5 to 7 to detect different batches of corn silk broken wall slice samples, record the chromatogram, import the chromatogram into the traditional Chinese medicine chromatographic fingerprint similarity evaluation system, screen and confirm the common peaks, and obtain the HPLC fingerprint of the corn silk broken wall slice.
10. A quality detection method for corn silk broken wall pieces, characterized in that: The following steps are involved: S1. Take the sample of corn silk broken wall slices to be tested, detect it using the high performance liquid chromatography analysis method according to any one of claims 5 to 7, record the chromatogram, and obtain the HPLC spectrum of the sample of corn silk broken wall slices to be tested; S2. The HPLC fingerprint of the corn silk broken wall slices according to claim 9 and the HPLC fingerprint of the corn silk broken wall slice sample to be tested are introduced into the Chinese medicine chromatographic fingerprint similarity evaluation system for comparison. The following two conditions are met to determine whether it is qualified: The HPLC spectrum of the corn silk broken wall slice sample to be tested presents a fingerprint peak whose relative retention time is within ±10% of the specified value in the HPLC fingerprint spectrum of the corn silk broken wall slice; The similarity between the HPLC spectrum of the corn silk broken wall slice sample to be tested and the HPLC fingerprint spectrum of the corn silk broken wall slice is calculated, and the similarity between the HPLC spectrum of the corn silk broken wall slice sample to be tested and the HPLC fingerprint spectrum of the corn silk broken wall slice is not less than 0.85; The HPLC fingerprint of the corn silk broken wall slices contains 18 fingerprint peaks, with peak 5 as the S peak, and the specified values of the relative retention time are: Peak No. 1 is 0.441, Peak No. 2 is 0.624, Peak No. 3 is 0.689, Peak No. 4 is 0.956, Peak No. 5 is 1.000, Peak No. 6 is 1.129, Peak No. 7 is 1.216, Peak No. 8 is 1.451, Peak No. 9 is 1.519, Peak No. 10 is 1.672, Peak No. 11 is 2.549, Peak No. 12 is 2.642, Peak No. 13 is 2.918, Peak No. 14 is 3.445, Peak No. 15 is 4.125, Peak No. 16 is 4.161, Peak No. 17 is 4.188, and Peak No. 18 is 4.257.
Citation Information
Patent Citations
Traditional Chinese medicine fingerprint spectrum inspection method of compound garden balsam stem preparations
CN109752478A
Compound lysimachia christinae hance granule UPLC quantitative fingerprint spectrum construction method
CN116699042A
Separation method of chemical components in corn stigma and preparation thereof or construction method of specific chromatogram
CN117741032A
Traditional Chinese medicine fingerprint spectrum of rhizoma anemarrhenae and cortex phellodendri cooling formula and construction method and application thereof
CN118858504A